Factors related to the incidence of diarrhea in children 1-5 years in the work area of Ujung Padang Health center, Simalungun district - Riada Mareny; Eka Sihombing; Nurmazdalifah; Diana Lorenta Barimbingan; Rina Valensi (Science Midwifery, 2022)
Diarrhea is a condition where the frequency of defecation is more than 4 (four) times in infants and more than 3 (three) times in children, the consistency of watery stools, can be green in color or can also be mixed with mucus and blood. Diarrheal disease is a health problem in developing countries, especially in Indonesia, both in rural and urban areas. Diarrhea is an endemic disease that often appears as an Extraordinary Event (KLB). Diarrheal disease is still a public health problem in developing countries such as Indonesia, because of its high morbidity and mortality. The morbidity survey conducted by the Sub-Directorate for Diarrhea, Ministry of Health from 2000 to 2010 shows an increasing trend of incidence. In 2000 (Incidence Ratio) IR Diarrhea disease 301/1000 population, in 2003 increased to 3741/1000 population, in 2006 increased to 423/1000 population and in 2010 to 411/1000 population. Research Objectives To determine the Factors Associated with the Incidence of Diarrhea in Children Under Five Years Old in the Puskesmas Area of Ujung Padang District, Simalungun Regency in 2016. This type of research is analytic with a cross sectional approach. The population of this study is mothers who have toddlers 1-5 years. The sample of this study were mothers who had toddlers aged 1-5 years who visited the Ujung Padang Health Center. The results of the study based on the results of the Chi-Sguare statistical test obtained the relationship between age and the incidence of diarrhea p value - 0.02 XS a (0.05), education with the incidence of diarrhea p value - 0.02 £« a (0.05), knowledge of incidence of diarrhea p value 0.00 X a (0.05), attitude towards the incidence of diarrhea p value 0.00 « a (0.05), behavior towards the incidence of diarrhea p value - 0.00 « a (0.05). So that it is known that there is a relationship between age, education, knowledge , attitudes , behavior towards the incidence of diarrhea in toddlers 1-5 years. It is hoped that the results of the research can become input and suggestions for health workers at the Ujung Padang Health Center in maintaining and improving health services, especially preventing diarrhea.